Analisis Green Purchases Intention Produk Bahan Bakar Ramah Lingkungan “Pertamax-Turbo” Di Surakarta - Muhammad Khoiruman; Ambar Wariati; Lukman Ahmad Imron Pahlawi (EXCELLENT, 2021)
Environmentally friendly products (eco-products or green products) are defined as products that have all physical and operational aspects at each stage of their life cycle - not harmful to the environment. Environmentally friendly products are designed, manufactured, and evaluated by applying all forms of innovation and technology that are focused on reducing the effects that are harmful to the environment (green product evaluation mechanism). . Pertamax Turbo is one of PERTAMINA's production fuels that meets environmentally friendly criteria. This research is descriptive analytic which aims to find out the variables that have a relationship with consumer awareness to buy environmentally friendly fuel products from Pertamax Turbo in Surakarta. The conclusions in this study are 1) Green Price and Eco-Product Knowledge variables have a direct and significant influence on Purchase Intention of consumers of Pertamax Turbo environmentally friendly fuels in Surakarta. 2) Belief in Environment Friendly Buying variables have a direct and insignificant influence on Purchase Intention Pertamax Turbo consumers of environmentally friendly fuels in Surakarta 3) Variable Attention towards Ecoproduct has a positive and significant effect on Purchase Intention of consumers of Pertamax Turbo environmentally friendly fuels in Surakarta. This causes the Attention towards Ecoproduct variable function as an intervening variable to be effective